(untitled) (Élisée - Revista de Geografia da UEG, 2020)
The new territorial division of work in cellulose and paper producing spacial circuits Abstract: This article aims to evidence the new territorial division of labor in the productive spacial circuits of cellulose and paper, that occurs both in scale global as well as national. On a global scale, the new division is marked by the transfer of forestry and cellulose production, early steps of the paper-producing spacial circuit, from the northern to the southern countries. At the national scale, its main characteristic refers to the internalization of forest and cellulose production incorporating new regions in the global paper productive spacial circuit. Moreover, it is also possible to observe that Brazil, due to comparative natural and artificial advantages, it has stood out in this new division of labor, becoming one of the leading producers of cellulose in the world. Keywords: Territorial division of labor. Productive spacial circuit. Cellulose. Paper.